Quetiapine v. lithium in the maintenance phase following a first episode of mania: Randomised controlled trial. (June 2017) - Berk, Michael; Daglas, Rothanthi; Dandash, Orwa; Yücel, Murat; Henry, Lisa; Hallam, Karen; Macneil, Craig; Hasty, Melissa; Pantelis, Christos; Murphy, Brendan P.; Kader, Linda; Damodaran, Saji; et al.
Abstract : Background: Lithium and quetiapine are considered standard maintenance agents for bipolar disorder yet it is unclear how their efficacy compares with each other. Aims: To investigate the differential effect of lithium and quetiapine on symptoms of depression, mania, general functioning, global illness severity and quality of life in patients with recently stabilised first-episode mania. Method: Maintenance trial of patients with first-episode mania stabilised on a combination of lithium and quetiapine, subsequently randomised to lithium or quetiapine monotherapy (up to 800 mg/day) and followed up for 1 year. (Trial registration: Australian and New Zealand Clinical Trials Registry – ACTRN12607000639426.) Results: In total, 61 individuals were randomised. Within mixed-model repeated measures analyses, significant omnibus treatment × visit interactions were observed for measures of overall psychopathology, psychotic symptoms and functioning. Planned and post hoc comparisons further demonstrated the superiority of lithium treatment over quetiapine. Conclusions: In people with first-episode mania treated with a combination of lithium and quetiapine, continuation treatment with lithium rather than quetiapine is superior in terms of mean levels of symptoms during a 1-year evolution.